Crematogaster pygmaea (Hymenoptera: Formicidae: Myrmicinae), a highly polygynous and polydomous Crematogaster from northeastern Brazil - Quinet, Yves; Hamidi, Rachid; Ruiz-Gonzalez, Mario Xavier; de Biseau, Jean-Christophe; Longino, John T. (Zootaxa, 2009)
Crematogaster pygmaea is revived from synonymy under C. abstinens and newly characterized as a ground-nesting ant from northeastern Brazil. It is a habitat specialist in coastal and tabuleiro zones, where it forms extensive polydomous and polygynous colonies that nest in the soil. Workers forage extensively on honeydew and extrafloral nectar, and foraging continues day and night, although it is depressed at ground temperatures above 32°C. Gyne production occurs at the beginning of the rainy season, while male production starts in the dry season, some months before gyne production.